Winning moves - "park, Louise" (Macmillan Education Australia: South Yarra, 2011)
Planet Aquare.s underwater world is being poisoned and the aquamantas are getting sick. When SC Star Girl is sent with her buddy SC Astron Girl to help they discover that looks can be deceiving. Can they find the source of the poison and stop it in time to save the planet and its alien aquamantas?
Keywords: Adventure stories